Research on active defense based on multi-stage cyber deception game - Yongjin HU; Jun MA; Yuanbo GUO; Han ZHANG (Tongxin xuebao, 2020)
In view of the characteristic that attacker depended on the detected information to decide the next actions,the non-cooperative signal game theory was applied to analyze cyber attack and defense.The signal deception mechanism in the process of cyber attack and defense was considered deeply by constructing a multi-stage cyber deception game model,and the dynamic analysis and deduction of the multi-stage cyber attack and defense was realized by considering the attenuation of cyber deception signals.A solution for multi-stage cyber deception game equilibrium was improved based on analysis of cyber attack and defense,and an optimal algorithm for selecting cyber deception defense strategies was designed.The effectiveness of the model is verified by simulations.The rules of multi-stage cyber deception games are summarized based on the results,which can provide effective guidance for the research on cyber active defense.